Lemma 36.6.12. With X, f_1, \ldots , f_ c \in \Gamma (X, \mathcal{O}_ X), and \mathcal{F} as in Remark 36.6.4. Let a_{ji} \in \Gamma (X, \mathcal{O}_ X) for 1 \leq i, j \leq c and set g_ j = \sum _{i = 1, \ldots , c} a_{ji}f_ i. Assume g_1, \ldots , g_ c scheme theoretically cut out Z. If \mathcal{F} is quasi-coherent, then
c_{f_1, \ldots , f_ c} = \det (a_{ji}) c_{g_1, \ldots , g_ c}
where c_{f_1, \ldots , f_ c} and c_{g_1, \ldots , g_ c} are as in Remark 36.6.10.
Proof.
We will prove that c_{f_1, \ldots , f_ c}(s) = \det (a_{ij}) c_{g_1, \ldots , g_ c}(s) as global sections of \mathcal{H}_ Z(\mathcal{F}) for any s \in \mathcal{F}(X). This is sufficient since we then obtain the same result for section over any open subscheme of X. To do this, for 1 \leq i_0 < \ldots < i_ p \leq c and 1 \leq j_0 < \ldots < j_ q \leq c we denote U_{i_0 \ldots i_ p} \subset X, V_{j_0 \ldots j_ q} \subset X, and W_{i_0 \ldots i_ p, j_0 \ldots j_ q} \subset X the open subscheme where f_{i_0} \ldots f_{i_ p} is invertible, g_{j_0} \ldots g_{j_ q} is invertible, and where f_{i_0} \ldots f_{i_ p}g_{j_0} \ldots g_{j_ q} is invertible. We denote \mathcal{F}_{i_0 \ldots i_ p}, resp. \mathcal{F}'_{j_0 \ldots j_ q} \mathcal{F}''_{i_0 \ldots i_ p, j_0 \ldots j_ q} the pushforward to X of the restriction of \mathcal{F} to U_{i_0 \ldots i_ p}, resp. V_{j_0 \ldots j_ q}, resp. W_{i_0 \ldots i_ p, j_0 \ldots j_ q}. Then we obtain three extended alternating Čech complexes
\mathcal{F}^\bullet : \mathcal{F} \to \bigoplus \nolimits _{i_0} \mathcal{F}_{i_0} \to \bigoplus \nolimits _{i_0 < i_1} \mathcal{F}_{i_0i_1} \to \ldots
and
(\mathcal{F}')^\bullet : \mathcal{F} \to \bigoplus \nolimits _{j_0} \mathcal{F}'_{j_0} \to \bigoplus \nolimits _{j_0 < j_1} \mathcal{F}'_{j_0j_1} \to \ldots
and
(\mathcal{F}'')^\bullet : \mathcal{F} \to \bigoplus \nolimits _{i_0} \mathcal{F}_{i_0} \oplus \bigoplus \nolimits _{j_0} \mathcal{F}'_{j_0} \to \bigoplus \nolimits _{i_0 < i_1} \mathcal{F}_{i_0i_1} \oplus \bigoplus \nolimits _{i_0, j_0} \mathcal{F}''_{i_0, j_0} \oplus \bigoplus \nolimits _{j_0 < j_1} \mathcal{F}'_{j_0j_1} \to \ldots
whose differentials are those used in defining (36.6.4.1). There are maps of complexes
(\mathcal{F}'')^\bullet \to \mathcal{F}^\bullet \quad \text{and}\quad (\mathcal{F}'')^\bullet \to (\mathcal{F}')^\bullet
given by the projection maps on the terms (and hence inducing the identity map in degree 0). Observe that by Lemma 36.6.7 each of these complexes represents i_*R\mathcal{H}_ Z(\mathcal{F}) and these maps represent the identity on this object. Thus it suffices to find an element
\sigma \in H^ c((\mathcal{F}'')^\bullet (X))
mapping to c_{f_1, \ldots , f_ c}(s) and \det (a_{ji})c_{g_1, \ldots , g_ c}(s) by these two maps. It turns out we can explicitly give a cocycle for \sigma . Namely, we take
\sigma _{1 \ldots c} = \frac{s}{f_1 \ldots f_ c} \in \mathcal{F}_{1 \ldots c}(X) \quad \text{and}\quad \sigma '_{1 \ldots c} = \frac{\det (a_{ji})s}{g_1 \ldots g_ c} \in \mathcal{F}'_{1 \ldots c}(X)
and we take
\sigma _{i_0 \ldots i_ p, j_0 \ldots j_{c - p - 2}} = \frac{\lambda (i_0 \ldots i_ p, j_0 \ldots j_{c - p - 2})s}{f_{i_0} \ldots f_{i_ p}g_{j_0} \ldots g_{j_{c - p - 2}}} \in \mathcal{F}''_{i_0 \ldots i_ p, j_0 \ldots j_{c - p - 2}}(X)
where \lambda (i_0 \ldots i_ p, j_0 \ldots j_{c - p - 2}) is the coefficient of e_1 \wedge \ldots \wedge e_ c in the formal expression
e_{i_0} \wedge \ldots \wedge e_{i_ p} \wedge (a_{j_01} e_1 + \ldots + a_{j_0c}e_ c) \wedge \ldots \wedge (a_{j_{c - p - 2}1} e_1 + \ldots + a_{j_{c - p - 2}c}e_ c)
To verify that \sigma is a cocycle, we have to show for 1 \leq i_0 < \ldots < i_ p \leq c and 1 \leq j_0 < \ldots < j_{c - p - 1} \leq c that we have
\begin{align*} 0 & = \sum \nolimits _{a = 0, \ldots , p} (-1)^ a f_{i_ a} \lambda (i_0 \ldots \hat i_ a \ldots i_ p, j_0 \ldots j_{c - p - 1}) \\ & + \sum \nolimits _{b = 0, \ldots , c - p - 1} (-1)^{p + b + 1}g_{j_ b} \lambda (i_0 \ldots i_ p, j_0 \ldots \hat j_ b \ldots j_{c - p - 1}) \end{align*}
The easiest way to see this is perhaps to argue that the formal expression
\xi = e_{i_0} \wedge \ldots \wedge e_{i_ p} \wedge (a_{j_01} e_1 + \ldots + a_{j_0c}e_ c) \wedge \ldots \wedge (a_{j_{c - p - 1}1} e_1 + \ldots + a_{j_{c - p - 1}c}e_ c)
is 0 as it is an element of the (c + 1)st wedge power of the free module on e_1, \ldots , e_ c and that the expression above is the image of \xi under the Koszul differential sending e_ i \to f_ i. Some details omitted.
\square
Comments (0)
There are also: